2019 International Conference on Robotics and Automation (ICRA) 2019
DOI: 10.1109/icra.2019.8794366
|View full text |Cite
|
Sign up to set email alerts
|

Robust Execution of Contact-Rich Motion Plans by Hybrid Force-Velocity Control

Abstract: In hybrid force-velocity control, the robot can use velocity control in some directions to follow a trajectory, while performing force control in other directions to maintain contacts with the environment regardless of positional errors. We call this way of executing a trajectory hybrid servoing. We propose an algorithm to compute hybrid force-velocity control actions for hybrid servoing. We quantify the robustness of a control action and make trade-offs between different requirements by formulating the contro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…1) Exerting Force: Forceful interaction involves exerting a wrench at a pose. While there are several control methods for this, such as force control [26] or hybrid position-force control [27], [28], we opt to use a Cartesian impedance controller. Cartesian impedance control treats the interplay of interaction forces and motion deviations as a massspring-damper system [29].…”
Section: B Constraints On Forceful Operationsmentioning
confidence: 99%
“…1) Exerting Force: Forceful interaction involves exerting a wrench at a pose. While there are several control methods for this, such as force control [26] or hybrid position-force control [27], [28], we opt to use a Cartesian impedance controller. Cartesian impedance control treats the interplay of interaction forces and motion deviations as a massspring-damper system [29].…”
Section: B Constraints On Forceful Operationsmentioning
confidence: 99%
“…By pressing a grasped object against a support, the robot can do in-hand manipulation [33,12,15,4] or transport the object without bearing its full weight [1,38]. Without a grasp, a finger can still move an object by planar pushing [19,41,11], pivoting or tumbling [30,14]. Dafle et al [7] demonstrated that a simple robot hand can do many tasks by sequencing multiple open loop actions with external contacts.…”
Section: A Manipulation Modeling With External Contactsmentioning
confidence: 99%
“…In [15] the authors introduce a Hybrid Force-Velocity Controller (HFVC) that can avoid unwanted transitions between contact modes by introducing friction cone constraints. The HFVC was further used in a shared grasping application [3] where a robot manipulator rotates a non-rigidly attached wooden block on its sides and corners.…”
Section: Related Workmentioning
confidence: 99%
“…Examples of in-hand manipulation include regulating the friction applied by the gripper on the object to swing it towards a desired angle [6]- [9], or slide it to a new contact point [10], [11]. Other examples exploit the interactions between object and environment to achieve a desired grasp [12]- [14], or to obtain a desired object configuration while in contact [3], [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation